SELF-HEALING SYSTEMS: APPLICATION AND METHODOLOGIES-A REVIEW - Ugwuanyi, Fidelis Onyebu; S. O, Anigbogu; Anigbogu, K. S (International Journal of Research -GRANTHAALAYAH, 2020)
Self-healing in software applications is patterned after the human cells which regenerates after a damage has been done to it. There are always attacks on software applications that sometimes render the user helpless, since most users are not technicians. If these applications will be able to recover from attacks and get back to normal state before it was attaced without letting the user know that such attack ever happened, a self-healing mechanism has been achieved in that application. In this paper, we tried to look at what is self-healing, methodologies that some researchers have proposed in order to achieve self-healing in any given system, system faults and its remedies, self-healing life cycle, and applications of self-healing in a system.